Modification of the Classical Theory of Metalworking - Vasilko, Karol; Murčinková, Zuzana (Manufacturing Technology Journal, 2021)
The paper derives mathematical and ggraphical relationships between technological parameters and result of metalworking, in the application of progresive cutting materials based on coated cutting tools of sintered carbide and cutting ceramits. The development of new cutting and machined materials leads to new perspectives on their interaction in the machining process. This process leads to patterns between cutting conditions and machined results. These need to be defined and used in favor of efficient machining of mechanical components in practice.
Keywords: machining; chip formation; tool durability; cutting forces; material machinability